Training of Primary School Teachers to Professional Mobility in Mountainous Region Conditions - Lutsan, Nadia (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The entry of Ukraine into the European educational space obliges all levels of education to respond quickly to new challenges: globalization (open space, competition in the labor market), innovation in science and technology sphere, the speed and frequency of communication of people in different areas that change individual environment and educational environment of the country. The system forming competitiveness and personality capable of human social and individual aspects to the fore follows such quality as creativity. Category creativity is one of the most important in recognizing the nature of mental mechanisms of human development and, in particular child. The paper analyzes the process of formation occupational mobility of the future expert that is based on model of modern teacher with considering his personal values and categories - art and creativity .